PERSONALITY TRAITS AS PREDICTORS OF MARITAL INSTABILITY AMONG MARRIED PERSONS IN BAYELSA CENTRAL SENATORIAL DISTRICT, BAYELSA STATE NIGERIA - Onyejiuwa Benjamin; Margaret Nzenye Elijah (PT. Antis International Publisher, 2026)
Objective : This study investigates personality traits as predictors of marital instability among married persons in Bayelsa Central Senatorial District, Bayelsa State Nigeria. Method : Correlational research design was used for the study. Five research questions and five null, hypotheses guided the study. The population of the study comprised all the married persons in Bayelsa Central Senatorial District, Bayelsa State, totaling 10,128. Fluid survey online calculator was used to determine sample size of 342 married persons for the study. Multi-stage sampling procedures were used for the study. Self-constructed instruments titled ‘Personality Traits, Marital Instability Scale’ (PTMIS) was used to collect data. The PT and MI Subscales were validated by research experts. The reliability of the instruments were determined through test re-test method that yielded indices of; conscientiousness 0.87, extroversion 0.82, openness to experience 0.85, neuroticism 0.81, agreeableness respectively. The researcher personally administered the instrument to the respondents with the help of research assistants in their various churches. Simple regression analysis was used to answer the five research questions and also tested the five corresponding null hypotheses at 0.05 level of significance using SPSS version 25. Results : The results revealed that; extroversion, openness to experience, neuroticism does significantly predict marital instability among married persons in Bayelsa central senatorial district, Bayelsa State, while conscientiousness, and agreeableness does not significantly predict marital instability among married persons in Bayelsa central senatorial district, Bayelsa State. Novelty : Based on the findings, the researcher recommends that counseling services should be tailored to address the impact of openness to experience, and neuroticism on marital relationships. Couples with higher levels of these traits could benefit from conflict resolution training and emotional regulation techniques to mitigate marital instability.